The art of public speaking : - Lucas, Stephen (McGraw-Hill, 2007)
Whether a novice or an experienced speaker, every student will learn how to be a better public speaker through Lucas' clear explanations and thorough coverage. By far the leading speech textbook of our time, The Art of Public Speaking has defined the art of being the best for more than six million students and instructors. The Lucas Learning Tools Suite offers even more tools and study options to fit the active lifestyles and diverse learning/teaching styles of today's students and instructors